2019
DOI: 10.1016/j.euromechsol.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Creep-fatigue and cyclically enhanced creep mechanisms in aluminium based metal matrix composites

Abstract: Reference transition hysteresis loops for the three cross-section studied. Finite element models, shakedown limit boundaries and load history applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Therefore, the n value in Equation (2) can be derived from Equation (1), which is plotted (on a log-log axis) in Figure 3. Information of the stress exponent n can be used to verify the creep mechanisms [20]. As shown in Figure 2 and Table 2, the creep of Al-Li alloys increases stepwise with aging time.…”
Section: Microstructure Observation and Characterizationmentioning
confidence: 99%
“…Therefore, the n value in Equation (2) can be derived from Equation (1), which is plotted (on a log-log axis) in Figure 3. Information of the stress exponent n can be used to verify the creep mechanisms [20]. As shown in Figure 2 and Table 2, the creep of Al-Li alloys increases stepwise with aging time.…”
Section: Microstructure Observation and Characterizationmentioning
confidence: 99%
“…The introduced hold time caused the transformation of high energy lath structure into more stable structure 33 . Dario et al 34 reported the cyclically enhanced creep mechanisms in aluminum‐based metal matrix composites. Goswami 35 reported the peak strain amplitude hold significantly affected the CFI life.…”
Section: Introductionmentioning
confidence: 99%
“…Validity and applicability of the LMM framework have been also acknowledged by a variety of commercial industry partners [25][26][27], in particular the LMM DSCA method has been selected by R5 research programme of EDF energy to the commercial standard [9]. In particular for the composite materials, the eDSCA was employed to analyse the cyclic creep and plastic behaviours [28][29][30]. Based on the reliability, the LMM eDSCA method is adopted for the numerical analysis in the present work.…”
Section: Direct Methods Employed For the Cyclic Plastic And Cyclic Crmentioning
confidence: 99%
“…Δt = 1hr, 10hrs, and 100hrs. When a dwell time is introduced within the thermal load history, different mechanisms can arise depending upon the loading condition applied and the state of stress at the matrix-reinforcement interface [41]. Indeed as reported in [24] within the shakedown boundary the structure can exhibit either shakedown or creep enhanced plasticity.…”
Section: Simulation Model Setupmentioning
confidence: 99%